Programa Bolsa Família, federalismo e poder local : o índice de gestão descentralizada municipal e o fator condicionalidade educação no município de Vitória (ES) - Kuyumjian, Andreia Leite (2016)
The implementation process of the Programa Bolsa Família suffers impact by its institutional design, decided at the federal level, as the different institutional capacities available at the local level, regarding the human resources, management and coordination among distinct services and available infrastructure. The bottlenecks found in the municipal levels, in general, related to the program quality coordination, were the motivation point of this research, held in Vitória (ES). Taking in consideration the Federal State scenery, the main goal of this study is to analyze the effectiveness of the Programa Bolsa Família from Decentralized Municipal Index (IGD-M), observing carefully the Education Conditionality, in this municipality. Qualitative methodology of exploratory nature was used at this documental research, in order to understand the control tools of this conditionality. The results indicate that the overall goals of the “Programa Bolsa Família” have been achieved, along the last years, in a positive and effective way at the Espírito Santo capital, through continuous dialogue and administrative actions, articulated among actors involved in the process.